GAMBARAN CITRA TUBUH DAN AKTIVITAS FISIK PADA SISWI SMP AL-ULUM PEKANBARU - Aritonang, Imelda Aldinur; ", Suyanto; Azrin, Miftah (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Abstractbody image is a mental image,perseption,the mind that owned by a person, for bodysize, body shape, and the body weight leads to pyhsical appearence. At theadolescence,physical growrth experiencing fast changing. It faster than childhood andat the grown up. These physical changes affect the body image of young women.Pysical activity Oral multidimensional complex forms of human behavior and thebehavior of the class rather than theoretically, covering all the gestures ranging fromsmall movements to participate in the marathon. lack of physical activity is anindependent risk factor for chronic diseases, and overall is estimated to cause of deathglobally. This research is a descriptive study that aims to describe body image andphysical activity in girls smp al-ulum pekanbaru. The study population was gradervii, viii, and IX smp al-ulum pekanbaru the sample amounted to 56 people who aredetermined by the total sampling method. Data collection was conducted on 9 Marchto 10 March 2015 through questionnaires filled out by the student and the height andweight measurements of respondents. This study used a questionnaire adoption tutirestuastuti (2011) obtained the result that the respondents were not satisfied with hissize is 31 people (55.36%) more than satisfied respondents amounted to 25 people.(44.64%). based on the existing nutritional status obtained underweight 18 people(32.14%), the normal 30 people (53.58%), overweght 5 people (8.92%) and obesityamounted to 3 people (5.36%). for physical activity obtained low activity of 31people (55.36% 0), moderate physical activity at least 21 people (37.5%) and highphysical activity as much as 4 people (7.14%).key words: body image, physical activity and nutritional status